2013
DOI: 10.1093/molbev/mst079
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Eye Transcriptome under Constant Darkness in Sinocyclocheilus Cavefish

Abstract: In adaptating to perpetual darkness, cave species gradually lose eyes and body pigmentation and evolve alternatives for exploring their environments. Although troglodyte features evolved independently many times in cavefish, we do not yet know whether independent evolution of these characters involves common genetic mechanisms. Surface-dwelling and many cave-dwelling species make the freshwater teleost genus Sinocyclocheilus an excellent model for studying the evolution of adaptations to life in constant darkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(110 citation statements)
references
References 78 publications
(119 reference statements)
7
95
2
Order By: Relevance
“…By comparing the genome of the Zebra Danio with close relatives, the role of mutations and gene expression can be determined. Comparative genomic studies within Cypriniformes have already benefited from the foundation and annotation of the Zebra Danio genome sequence to generate insights into the functional evolution of various adaptations including adaptation to harsh environments such as caves and high altitude streams [82, 83]. With a robust phylogeny, we can get a much better understanding of the function of genes by treating relatives of the Zebra Danio as natural mutants screened by natural selection [1].…”
Section: Discussionmentioning
confidence: 99%
“…By comparing the genome of the Zebra Danio with close relatives, the role of mutations and gene expression can be determined. Comparative genomic studies within Cypriniformes have already benefited from the foundation and annotation of the Zebra Danio genome sequence to generate insights into the functional evolution of various adaptations including adaptation to harsh environments such as caves and high altitude streams [82, 83]. With a robust phylogeny, we can get a much better understanding of the function of genes by treating relatives of the Zebra Danio as natural mutants screened by natural selection [1].…”
Section: Discussionmentioning
confidence: 99%
“…Sinocyclocheilus ronganensis, a cavefish and is newly found in the karst river of Rong'an county, Southwestern China (Luo et al 2016). Like other surface-dwelling species (Zhao & Zhang 2009;Meng et al 2013), S. ronganensis has normal eyes, full-cover scales but larger than most of them, and it is a good model for studying the genetic status and evolutionary by comparing the mitochondrial genome.…”
Section: Introductionmentioning
confidence: 99%
“…When studying the adult forms of one cavefish species of this genus (S. anophthalmus), it was discovered that they possess regressed eyes similarly buried under the skin as they are in Astyananx, but the overall eye structure remained intact. The authors reported fully formed lenses, cornea, iris and retinal structures, even though the retina was notably thinner than in surface fish [6,69].…”
Section: Work On Other Cavefish Speciesmentioning
confidence: 92%